Upaya Meningkatkan Perkembangan Kognitif Anak Usia Dini dalam Pembelajaran Pai Melalui Pendekatan Beyond Centers And Circle Time (BCCT) - Asih Wahyuni (LPPM IAIN Sorong, 2018)
This paper discusses the improvement of children's cognitive in learning of PAI using BCCT (Beyond Centers and Circle Time) approach. In this approach, the child is stimulated to actively perform the play activities while learning in the learning centers. Center a made based on the needs and development of children. Some centers used include 1) central role play; 2) beam center; and 3) worship centers; 4) preparation center; 5) art creativity center; and 6) centers of natural materials. The results of the study indicate that the BCCT approach improves children's cognitive development with the support of this approach.